Study the atomic properties of 2s shell for some atoms - Kadhim, Shaymaa Awad (Iraqi Journal of Physics, 2019)
Ground state energies and other properties of 2S shell for some atoms as Be(Z=4), B(Z=5), C(Z=6) and N(Z=7) were calculated by using Hartree-Fock wave function. We found the values of potential energies in hartree unit (3.8369, 6.78565, 10.18852 and 14.41089) respectively and the other proprieties like expectation values of the position < r1m > were in agreement with the published results. All the studied atomic properties were normalized.